Classification of homes according to health profile for the purpose of prevention, promotion and recovery resource focus, Medellin, 2004 - Ángela M. Segura; Ilduara Peña; Elsa M. Vásquez (Universidad de Antioquia, 2008)
Objective: to obtain a health profile to classify homes of Medellín city, according to similarities due to life and health conditions. Materials and methods: for the creation of a health profile, information was taken from the data collected in the Quality of Life Survey, Medellín, 2004, where variables referring to life conditions and health determinants were selected. An analysis of mean components was made to choose those that explained the greater variability among homes, then a cluster analysis in 2 steps was performed to group the homes according to their life and health conditions. Results: the observed correlations appeared in the expected directions. A total of 12 components explain 69% of the variability of the data, contributing to a greater proportion of variability the variables of life conditions. In Medellín, 5 types of homes were identified sharing the same conditions of life and health. Conclusion: multivariant techniques allow to conclude that Medellín's home classification into 5 types regarding their determinants of health provides opportunities to make formulation of intervention programs at the population level possible.